Central bank digital currency: When price and bank stability collide - Jesús Fernández-Villaverde; Linda Schilling; Harald Uhlig (European Central Bank (ECB), 2024)
This paper shows the existence of a central bank trilemma. When a central bank is involved in financial intermediation, either directly through a central bank digital currency (CBDC) or indirectly through other policy instruments, it can only achieve at most two of three objectives: a socially efficient allocation, financial stability (i.e., absence of runs), and price stability. In particular, a commitment to price stability can cause a run on the central bank. Implementation of the socially optimal allocation requires a commitment to inflation. We illustrate this idea through a nominal version of the Diamond and Dybvig (1983) model. Our perspective may be particularly appropriate when CBDCs are introduced on a wide scale.
Keywords: E58; G21; 330; CBDC; currency crises; monetary policy; bank runs; spending runs; financial intermediation; central bank digital currency; inflation targeting